Bridge-Induced Translocation between NUP145 and TOP2 Yeast Genes Models the Genetic Fusion between the Human Orthologs Associated With Acute Myeloid Leukemia - Tosato, Valentina; West, Nicole; Zrimec, Jan; Nikitin, Dmitri V.; Del Sal, Giannino; Marano, Roberto; Breitenbach, Michael; Bruschi, Carlo V. (Frontiers in Oncology, 2017)
In mammalian organisms liquid tumors such as Acute Myeloid Leukemia (AML) are related to spontaneous chromosomal translocations ensuing in gene fusions. We previously developed a system named BIT (Bridge-Induced Translocation) that allows linking together two different chromosomes exploiting the strong endogenous homologous recombination system of the yeast Saccharomyces cerevisiae. The BIT system generates a heterogeneous population of cells with different aneuploidies and severe aberrant phenotypes reminiscent of a cancerogenic transformation. In this work, thanks to a complex pop-out methodology of the marker used for the selection of translocants, we succeeded by BIT technology to precisely reproduce in yeast the peculiar chromosome translocation that has been associated with AML, characterized by the fusion between the human genes NUP98 and TOP2B. To shed light on the origin of the DNA fragility within NUP98, an extensive analysis of the curvature, bending, thermostability and B-Z transition aptitude of the breakpoint region of NUP98 and of its yeast ortholog NUP145 has been performed. On this basis, a DNA cassette carrying homologous tails to the two genes was amplified by PCR and allowed the targeted fusion between NUP145 and TOP2, leading to reproduce the chimeric transcript in a diploid strain of Saccharomyces cerevisiae. The resulting translocated yeast obtained through BIT appears characterized by abnormal spherical bodies of nearly 500 nm of diameter, absence of external membrane and defined cytoplasmic localization. Since Nup98 is a well-known regulator of the post-transcriptional modification of P53 target genes, and P53 mutations are occasionally reported in AML, this translocant yeast strain, can be used as a model to test the constitutive expression of human P53. Although the abnormal phenotype of the translocant yeast was never rescued by its expression, an exogenous P53 was recognized to confer increased vitality to the translocants, in spite of its usual and well-documented toxicity to wild type yeast strains. These results obtained in yeast could provide new grounds for the interpretation of past observations made in leukemic patients indicating a possible involvement of P53 in cell transformation toward AML.